Partilha de néctar de Eucalyptus spp., territorialidade e hierarquia de dominância em beija-flores (Aves: Trochilidae) no sudeste do Brasil - Antunes, Alexsander Z. [UNESP] (2003)
Territorial behavior in hummingbirds minimizes competition through aggressive interactions, resulting in a dominance hierarchy among species and individuals. Interactions among seven hummingbird species visiting flowering eucalyptus in the Floresta Estadual near Rio Claro, São Paulo, in southeastern Brazil, were studied. Dominance was determined by weight and size with the largest species being the most dominant. Time spent in defense and the number of aggressive interactions were greater than recorded in literature, perhaps due to the relatively greater density of hummingbirds in the study area. Daily activity patterns differed among dominant and subordinate species, but were not correlated with either the quantity of available nectar or with nectar sugar concentration.